Characterization of kenaf fiber and its composites: A review. (June 2018) - Ramesh, P; Durga Prasad, B; Narayana, KL
Nowadays, fiber-reinforced composites have gained attention due to their improved potential for replacing the conventional materials in various applications. Kenaf fiber has been widely used as reinforcement in composites over the past few years which is a most attractive alternative due to its rapid growth at different climatic conditions and ensuring low cost; kenaf fiber has gained some attention to replacing the glass fiber composite and making it purely an eco-friendly composite. However, for enhancing its properties in different applications, an appropriate characterization is very important. Hence, many researches have been conducted in recent years, for the characterization of kenaf fiber and its composites. In this paper, a state-of-the-art review of these characterizations is presented.